Laparoscopic versus open liver resection for hepatocellular carcinoma in elderly patients: A systematic review and meta-analysis of propensity score-matched studies - Wang, Shi; Ye, Guanxiong; Wang, Jun; Xu, Shengqian; Ye, Qiaoping; Ye, Hailin (Frontiers in Oncology, 2022)
Purpose: The Laparoscopic liver resection (LLR) is a widely practiced therapeutic method, it holds several advantages over open liver resection (OLR) including less postoperative pain, lower morbidity, and faster recovery. However, the effect of LLR for the treatment of hepatocellular carcinoma (HCC) in elderly patients remains controversial. Therefore, we aimed to perform the first meta-analysis of propensity-score matched (PSM) studies to compare the short- and long-term outcomes of LLR versus OLR for elderly patients with HCC. Methods: Databases including PubMed, Embase, Scopus, and Cochrane Library were systematically searched until April 2022 for eligible studies that compared LLR and OLR for the treatment of HCC in elderly patients. Short-term outcomes including postoperative complications, blood loss, surgical time, and length of hospital stay. Long-term outcomes including overall survival (OS) rate and disease-free survival (DFS) rate at 1-, 3- and 5-year. Results: A total of 12 trials involving 1861 patients (907 in LLR group, 954 in OLR group) were included. Compared with OLR, the LLR was associated with lower postoperative complications (OR 0.49, 95%CI 0.39 to 0.62, P<0.00001, I2=0%), less blood loss (MD -285.69, 95%CI -481.72 to -89.65, P=0.004, I2=96%) and shorter hospital stay (MD -7.88, 95%CI -11.38 to -4.37, P<0.0001, I2=96%), whereas the operation time (MD 17.33, 95%CI -6.17 to 40.83, P=0.15, I2=92%) were insignificantly different. Furthermore, there were no significant differences for the OS and DFS rate at 1-, 3-, and 5-year. Conclusions: For elderly patients with HCC, LLR offers better short-term outcomes including lower incidence of postoperative complications and shorter hospital stays, with comparable long-term outcomes when compared to open approach. Our results support the implementation of LLR for the treatment of HCC in elderly patients.